Development of Ibn Taymiyyah’s ideas in the works of Sayyid Qutb (1906-1966) - Maevskaya, Ludmila B.; Aga, Khaisam Muhammad (Linguistics and Culture Review, 2021)
In modern Islam, Sayyid Qutb is considered one of the main ideologues of fundamentalism. S. Qutb reinterpreted traditional Islamic concepts for use in political activities. His ideas had a huge impact on the jihadist takfiris. In turn, the worldview and subsequent political concepts of Qutb himself were formed under the influence of many medieval thinkers, including Ibn Taymiyyah. Since the study of the influence of Ibn Taymiyyah on the worldview of this religious and political figure has not received sufficient attention from researchers, this determines the relevance of this work. The purpose of the study is to study the influence of the ideas of Ibn Taymiyyah on S. Qutb, and his interpretation of the teachings of this religious figure. The scientific novelty lies in a comprehensive study of the influence of Ibn Taymiyyah’s ideas on the worldview of S. Qutb. In the course of studying this issue, the following methods of scientific research were used: analysis, comparison, chronology, historical-comparative method, which contributed to the establishment of objective and subjective factors that influenced the formation of the teachings of Ibn Taymiyyah and Sayyid Qutb.